Antidepressant-Like Effect of Bauhinia blakeana Dunn in a Neuroinflammation Model in Mice - Herrera-Ruiz, Maribel (Med Princ Pract, 2020)
OBJECTIVE: To evaluate the antidepressant effect of Bauhinia blakeana and a standardized fraction in the forced swimming test (FST) on mice with neuroinflammation induced with lipopolysaccharides (LPS). MATERIALS AND METHODS: Evaluation of the antidepressant effect of Bauhinia blakeana hydroalcoholic extract (BbHA) and its fractions was carried out in behavioral tests on mice with LPS-induced neuroinflammation. RESULTS: BbHA had a significant antidepressant effect, measured on healthy mice in the FST. Bio-guided chemical separation of the extract produced a methanolic fraction (BbMe), which decreased the immobility time in FST. In this test, the intraperitoneal administration of LPS induced depression in mice, and BbHA and BbMe counteracted this effect, significantly decreasing the induced depression. Quantification of inflammatory mediators (IL-10, IL-4, IL-6, IL-1β, and TNF-α) in the brain demonstrated that BbHA and BbMe effectively decreased the effect of LPS on the brain concentration of all measured cytokines. CONCLUSIONS: Bauhinia blakeana produced an antidepressant effect, while BbMe also exerted a modulating effect, on the damage induced by LPS. Rutin, a glycosylated flavonoid, was identified as the main compound in the active fraction, which could mediate in the antidepressant and immunomodulatory effect.